Kakovost življenja starih ljudi s kroničnimi obolenji - Filej, Bojana (Kakovostna starost, 2015)
The aim of the study was to identify how chronical illnesses influence the quality of life of the elderly. Data collection was based on quantitative research approach. The descriptive causal non-experimental method was used. In order to establish the quality of life of the respondents, SF 36 questionnaire was used. The final sample consisted of 100 respondents above the age of 65, 38 % of whom were men and 62 % women. With the Pearson correlation coefficient we established the correlation between the two variables (the number of chronic illnesses and the number od achieved points when evaluating the quality of life level). The results have shown that with the increased number of chronic illnesses there is a decrease in the quality of life level in all the measured areas of health, that the component %physical health% was lower rated than the component %mental health%, and that the quality of life is higher in men. Taking into consideration the measured areas of health, we have discovered that at the occurrence of a chronic illness not only nursing care (physical support) is neccessary, but also psychological, emotional and social care and support.
Keywords: kakovost življenja; quality of life; standard of living; stari ljudje; older people; chronic illnesses; kronične bolezni